2013
DOI: 10.1136/bmj.f2743
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a bundled intervention of decolonization and prophylaxis to decrease Gram positive surgical site infections after cardiac or orthopedic surgery: systematic review and meta-analysis

Abstract: Objective To evaluate studies assessing the effectiveness of a bundle of nasal decolonization and glycopeptide prophylaxis for preventing surgical site infections caused by Gram positive bacteria among patients undergoing cardiac operations or total joint replacement procedures.Design Systematic review and meta-analysis. PubMed (1995PubMed ( to 2011, the Cochrane database of systematic reviews, CINAHL, Embase, and clinicaltrials.gov were searched to identify relevant studies. Pertinent journals and conference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
121
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(130 citation statements)
references
References 68 publications
(37 reference statements)
2
121
0
7
Order By: Relevance
“…Two systematic literature reviews and meta-analyses of published studies found a protective effect of mupirocin decolonization against surgical site infections (SSIs), especially among nongeneral surgery such as cardiac surgery, orthopedic surgery, and neurosurgery (38,42). (see Decolonization Prior to Surgery below for additional information) Two other meta-analyses found that decolonization with nasal mupirocin alone or in combination with topical agents such as CHG decreased the odds of S. aureus infection by approximately 60% among dialysis patients (39,44).…”
Section: Mupirocinmentioning
confidence: 99%
See 3 more Smart Citations
“…Two systematic literature reviews and meta-analyses of published studies found a protective effect of mupirocin decolonization against surgical site infections (SSIs), especially among nongeneral surgery such as cardiac surgery, orthopedic surgery, and neurosurgery (38,42). (see Decolonization Prior to Surgery below for additional information) Two other meta-analyses found that decolonization with nasal mupirocin alone or in combination with topical agents such as CHG decreased the odds of S. aureus infection by approximately 60% among dialysis patients (39,44).…”
Section: Mupirocinmentioning
confidence: 99%
“…More studies have evaluated decolonization among surgical patients than among any other patient population (38,42,44). Studies have shown that decolonization can decrease the incidence of Gram-positive SSIs after some types of surgery (38,149).…”
Section: Decolonization Prior To Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, MRSA carriers act as reservoirs for the transmission of MRSA between hospitalized patients. Preoperative S. aureus screening and decolonization regimens for those undergoing selected surgeries have been advocated to decrease the infection risk in carriers (3,4). Decolonization therapy can also be a successful infection control strategy to limit MRSA transmission within hospitals (5).…”
mentioning
confidence: 99%